Starting shift control of heavy-duty automatic transmissions based on the optimal trajectory of turbine speed. (1st July 2019) - Li, Chunfu; Meng, Fei; Xi, Junqiang; Zhai, Yong
Highlights: The starting shift process related to the turbine torque and speed is analyzed. The ideal trajectory of the turbine speed of the starting shift is investigated. A control strategy for the starting shift process is proposed. The control strategy is verified by real vehicle test. Abstract: Automatic transmission (AT) is one type of multiple speed transmissions which can transmit continuous power as well as torque adaptation. This paper proposes a novel control strategy for the starting shift process, which is capable of realizing better shift performance in practice. In order to reduce the shift jerk, firstly, the reasons of shift jerk during starting shift process which is relate to the turbine torque and speed is analyzed based on the system dynamical model. And divides the starting shift control process into four stages: the rapid oil-filling phase, the turbine speed slow descent phase, the closed-loop control phase and the clutch fully engagement phase. The ideal trajectory of the turbine speed during the starting shift process is also analyzed, and the causes of shift jerk in stage of the turbine speed begins to decline and clutch fully engagement phase are investigated. The ideal trajectory equation of the turbine speed in the closed-loop control phase is deduced. This paper presents a control strategy for the starting shift process, the T-S fuzzy control strategy is adopted in the turbine speed slow descent phase, and the digital recursive PID control strategy based on the ideal target trajectory of the turbine speed is adopted in the closed-loop control phase. The feasibility of the control strategy is verified by real vehicle test. This paper provides a simple and effective control strategy for AT shifting process control, and presents a method for calculating the starting shift jerk.